Implementasi Sistem Pakar Untuk Mendeteksi Kerusakan Mesin Pemanggang Roti Menggunakan Metode Teorema Bayes - Mukhlis Ramadhan; Hendra Jaya; Ismawardi Santoso (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
PT Arma Anugrah Abadi is a company engaged in bakery which is quite large in the city of Medan and has several branches in the city of Medan. With large companies in the process of production, they have equipment, equipment and a large enough workforce in the production section. The production is large enough to require maintenance in checking the damage to the Heng Wei GOM 200 toaster machine. Based on the observations made, the lack of public knowledge about the toaster machine causes the bread business actors to experience problems in running their business, and with the delay in handling the business, the business has stopped. with the problem of a broken bread machine. In this case, we need a method that is capable and tested in detecting damage to the toaster machine to conclude the results of the decision using the Expert System concept. An expert system or known as a knowledge based system is something that is meant to take decisions or solve problems to detect malfunctions of a toaster machine. The Expert System method can be developed in an effort to detect damage to the Heng Wei Brand Toaster Machine Type GOM 200 by using the Bayes Theorem method. The results of the Bayes theorem method can detect damage to the toaster machine on a toaster machine by calculating the uncertainty of the data to be certain or detect a malfunction